Just one day - Forman, Gayle (New York : Dutton Books, 2013)
"Sparks fly when American good girl Allyson encounters laid-back Dutch actor Willem, so she follows him on a whirlwind trip to Paris, upending her life in just one day and prompting a year of self-discovery and the search for true love."
Sequel: Just one year.
Keywords: Voyages and travels -- Fiction; Self-actualization (Psychology) -- Fiction; Love -- Fiction; Actors and actresses -- Fiction; Europe -- Fiction